2010
DOI: 10.4993/acrt.18.28
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Circadian Rhythm of Human Vascular Endothelial Growth Factor by Circadian Rhythm of Hypoxia Inducible Factor-1α : Implication for Clinical Use as Anti-Angiogenic Therapy

Abstract: Angiogenesis is essential for tumor growth and metastasis, therefore, inhibition of angiogenesis has emerged as a new therapy to treat cancers. Although vascular endothelial cell growth factor (VEGF) induces tumor growth and metastasis by its angiogenic property, the mechanism(s) of circadian rhythm in angiogenesis has not been fully analyzed. Here we revealed that VEGF mRNA expression level, protein expression level and its promoter activity belonged to circadian rhythm in human colon carcinoma cell line, HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…These in turn downregulate their own expression and allow for a new cycle of the feedback loop with a period of approximately 24 h (Idda et al 2012). Among the transcripts evidencing a rhythmic, circadian expression pattern, several genes were identified that are also known to be under the control of the hypoxic signaling pathway, such as, for example, erythropoietin (epo) and vascular endothelial growth factor (vegf; Bozek et al 2009;Fujita et al 2010;Jensen et al 2012). In normoxic zebrafish the mRNA expression of epo and veg f165 also underlies a diurnal expression pattern; epo mRNA, for example, is mostly produced during the night phase.…”
Section: Influence Of Circadian Rhythms On Hif Expressionmentioning
confidence: 99%
“…These in turn downregulate their own expression and allow for a new cycle of the feedback loop with a period of approximately 24 h (Idda et al 2012). Among the transcripts evidencing a rhythmic, circadian expression pattern, several genes were identified that are also known to be under the control of the hypoxic signaling pathway, such as, for example, erythropoietin (epo) and vascular endothelial growth factor (vegf; Bozek et al 2009;Fujita et al 2010;Jensen et al 2012). In normoxic zebrafish the mRNA expression of epo and veg f165 also underlies a diurnal expression pattern; epo mRNA, for example, is mostly produced during the night phase.…”
Section: Influence Of Circadian Rhythms On Hif Expressionmentioning
confidence: 99%
“…In mammals, HIF‐1 has been described as a factor with overrepresented binding sites in the promoters of clock‐controlled genes (CCGs) (23), and an HIF‐1‐dependent circadian rhythm has been recently reported with respect to mRNA and promoter activity in human cells (24). Although we did not measure the HIF‐1α circadian variations in the current study, the differences between the HIF‐1α abundance at 08:00 and 20:00 under all of the experimental conditions (although the differences were not statistically significant because of the high standard errors), and particularly under DD, suggest an HIF‐1α circadian rhythm in the central oscillators of crayfish.…”
Section: Discussionmentioning
confidence: 99%
“…While it has not been demonstrated that the disruption in BMAL1 signalling is the cause of ischaemia‐induced angiogenesis, these findings suggest that ROR‐α may be a negative regulator of ischaemia‐induced angiogenesis 83 . The regulation of VEGF‐A mRNA and VEGF‐A protein expression levels by the circadian fluctuations of HIF‐α has been confirmed in a human colon cancer cell line following serum shock 84 . Indeed, studies using human cell lines identified BMAL2 and CLOCK as key regulators of VEGF‐A, with levels of VEGF‐A peaking during the night 85,86 .…”
Section: Exploiting the Circadian Clock To Personalised Anti‐angiogen...mentioning
confidence: 94%
“…83 The regulation of VEGF-A mRNA and VEGF-A protein expression levels by the circadian fluctuations of HIFα has been confirmed in a human colon cancer cell line following serum shock. 84 Indeed, studies using human cell lines identified BMAL2 and CLOCK…”
Section: E Xploiting the Circ Ad Ian Clo Ck To Per Sonalis Ed Anti -A...mentioning
confidence: 99%